Analisis Campur Kode dan Alih Kode pada Akun Instagram “OVERHEARDJKT” - Sirikanda Sakulpimolrat; M.R. Nababan (PRASASTI: Journal of Linguistics, 2026)
This is a descriptive qualitative study that aims to describe the forms and causes of code-mixing and code-switching in posts from the Instagram account "overheardjkt" between February and March 2025. Data were collected through documentation and note-taking, focusing on words, phrases, and sentences related to code-mixing and code-switching. The analysis revealed 23 instances of code-mixing (11 at the word level, 11 at the phrase level, and 1 blend) and 3 instances of external code-switching (2 at the phrase level and 1 at the sentence level). The causes were identified as linguistic factors such as the absence of suitable equivalents, communication efficiency, and emphasis, and social factors, including urban lifestyle and globalization, prestige, group solidarity, and humor.